A Shear Strength Model for a Subsidence Backfill Body Based on Adhesion Friction Theory - Lei Liu; Shengyou Zhang; Weidong Liu; Wei Sun; Jinxin Li (Advances in Civil Engineering)
Proper determination of the shear strength of the backfill body used to fill the subsidence is the basis for subsidence restoration and the stability analysis of materials. This study developed a shear strength calculation model for the backfill body by introducing adhesive friction theory into the shear strength analysis. A direct shear test was performed in the laboratory to verify the proposed method. Test results suggested that the shear strength calculation method based on adhesive friction theory can calculate the variation in the actual contact area between grains in the tested samples undergoing shearing and estimate the peak shear strength. The actual contact area was divided into two components, namely, adhesive contact area Arm and contact area reduction caused by shear displacement, which exhibited a maximum at Armax. The shear strength values calculated by this method were smaller than laboratory values, and their differences increased with the rock proportion in the backfill body. The differences between the theoretical and experimental values of shear strength increased with the rock grain size. The results of theoretical calculation, combined with the results of laboratory experiments, can provide support for the proper determination of shear strength of the backfill body.